Effect of neonatal sepsis on platelet counts and their indices - Mevundi, Gonesh N.; S., Harsha (International Journal of Contemporary Pediatrics, 2020)
Background: Neonatal septicemia is a clinical syndrome characterized by signs and symptoms of infection with or without accompanying bacteremia in the first month of life. Objective of the study was to know the effect of sepsis on platelet counts and their indices. Methods: The study was carried out over a period of one and half year from December 2015 to July 2017 at Sangmeshwar and Basaveshwar hospital attached to M. R. medical college, Kalaburagi. 100 cases were considered for this study after proper screening for complete blood count (CBC), platelet count and their indices like mean platelet volume, platelet distribution width and C-reactive protein (CRP) and blood culture in neonates admitted in our neonatal intensive care unit (NICU) with proven sepsis. Results: A total of 100 neonates with blood culture positive for bacterial cases were considered for the study. Early onset septicaemia (59%) was more common than late onset septicaemia (41%). Out of 100 cases 57% cases had growth of gram negative organisms, 40% had growth of gram positive organisms and 3% had growth of fungal. Tachypnea (27%), lethargy (20%) and refusal of feeds (8%) were the commonest clinical presentation followed by, fever (6%), convulsions (5%) and jaundice (5%). 60% neonates had thrombocytopenia of varying severity. Staphylococcus aureus was the most common organism associated with thrombocytopenia (43.3%). Mean platelet volume (MPV) was high in 85% of cases and platelet distribution width (PDW) was high in 96% of cases. Conclusions: The present study highlights the association of thrombocytopenia, mean platelet volume and platelet distribution width with causative organism in proven neonatal sepsis. Staphylococcus aureus was the most common organism causing thrombocytopenia in our NICU.